Sex and Age Differences in the Impact of Metabolic Syndrome on Heart Failure Development - Tae-Eun Kim; Do Young Kim; Hyeongsu Kim; Sung Hea Kim (Metabolites)
Metabolic syndrome (MetS), a cluster of metabolic dysregulations, is recognized as a significant risk factor for the development of heart failure (HF). The pathophysiological mechanisms linking MetS to HF are complex and multifaceted, with the components of MetS contributing to cardiac deterioration through impaired myocardial energy metabolism, increased inflammation, and endothelial dysfunction. Numerous clinical studies have confirmed the relationship between MetS and HF. Multiple studies have demonstrated that the impact of MetS on HF varies by sex and age. Metabolic disorders, including MetS, have a greater impact on HF incidence in younger adults compared to the elderly population and in women compared to men. Although the reasons for these differences are not yet fully understood, recognizing the sex- and age-related variations is crucial for developing targeted strategies to prevent HF in individuals with MetS. Future research should continue to investigate the underlying mechanisms behind these variations and identify optimal management approaches that account for both sex and age in reducing HF risk.